To determine which expression is not equivalent to the others, let's simplify each expression:
-
Expression 1: \( 8x - x - 6 \)
- Simplifying: \[ 8x - x = 7x \Rightarrow 7x - 6 \]
-
Expression 2: \( 2x + 2 + 2x + 3x - 8 \)
- Simplifying: \[ 2x + 2x + 3x = 7x \Rightarrow 7x + 2 - 8 = 7x - 6 \]
-
Expression 3: \( 4 + 7x - 2 \)
- Simplifying: \[ 4 - 2 = 2 \Rightarrow 7x + 2 \]
-
Expression 4: \( -2 + 5x + 2x - 4 \)
- Simplifying: \[ -2 - 4 = -6 \quad \text{and} \quad 5x + 2x = 7x \Rightarrow 7x - 6 \]
Now, let's summarize the results:
- Expression 1 simplifies to \( 7x - 6 \)
- Expression 2 simplifies to \( 7x - 6 \)
- Expression 3 simplifies to \( 7x + 2 \)
- Expression 4 simplifies to \( 7x - 6 \)
The only expression that does not match the others is Expression 3: \( 4 + 7x - 2 \), which simplifies to \( 7x + 2 \).
Thus, the expression that is not equivalent to the other three is:
4 + 7x - 2.